Analisis Pendahuluan Literasi Sains pada Fluida di SMAN 6 Padang - Muhammad Dhanil; Fatni Mufit (Postgraduate, University of Mataram, 2023)
One of the 21st-century skills that students must master is scientific literacy. A good mastery of scientific literacy helps solve real-world problems. However, the results of PISA 2018 inform that Indonesian students' scientific literacy is relatively low. This study aims to analyze students' physics scientific literacy on fluid materials. Quantitative descriptive methods using fluid material scientific literacy test instruments were used to collect data. The research sample consisted of 36 students at SHS 6 Padang. The use of students' scientific literacy in the context aspect was 35.5% in the low category, the content was 35.7% in the low category, and the competency category was 35.3% in the low category. So, students' mastery of scientific literacy on fluid materials is in a low category.